Bajka polska : od Kadlubka do Herberta - Woznowski, Waclaw; Bernat, Miroslawa (Wroclaw : Zaklad Narodowy im. Ossolinskich, 1992)
An overview of Polish folklore throught the centuries, from the 10 th to the 20th.
Includes bibliographical references (p. 12).
Keywords: Fables, Polish; Polish poetry